Privacidade e relações públicas no contexto da comunicação digital - Maso, Nicole Sachet (My University, 2020)
The theme of the work is privacy and public relations in the context of digital communication. It is understood as a general objective the analysis of the Public Relations professional in the performance to deliver content from more strategic campaigns based on personal data and searches on the internet without affecting the privacy of their audiences. For that, it was necessary to understand how users perceived in relation to the exposure of information on the internet and even when they understood that their privacy could be invaded. For a better development, a bibliographic review on public relations and media, public relations deontology, the concepts of big data, privacy, remarketing and the new Data Protection Law were carried out. The monograph takes a quantitative approach with the aim of identifying the users' perception of campaigns on social networks. The research process started with the phase of data collection, exploratory research on social networks and a case report on the Facebook platform. As a result, the importance of collecting information and data was identified in order to bring users personalized products and services, restricting themselves to the use of methods such as cameras and microphones, which according to the user's perception is a very invasive action. In this way, it remains for the Public Relations professional to create and segment certain and effective strategies in campaigns to reach more specific audiences, without hurting the user's privacy. [resumo fornecido pelo autor]
O trabalho possui como tema a privacidade e relações públicas no contexto da comunicação digital. Compreende-se como objetivo geral a análise do profissional de Relações Públicas na atuação para entregar conteúdo de campanhas mais estratégicas a partir de dados pessoais e buscas na internet sem afetar a privacidade de seus públicos. Para isso foi necessário compreender como os usuários percebiam em relação a exposição de informações na internet e até quando compreendiam que a privacidade deles poderia ser invadida. Para um melhor desenvolvimento realizou-se uma revisão bibliográfica sobre relações públicas e mídias, deontologia das relações públicas, os conceitos de big data, privacidade, remarketing e a nova Lei de Proteção de Dados. A monografia assume uma abordagem quantitativa com o objetivo de identificar a percepção dos usuários sobre as campanhas nas redes sociais. O processo de pesquisa iniciou com a fase de coleta de dados, pesquisa exploratória das redes sociais e relato de caso da plataforma do Facebook. Como resultados foram identificados a importância da coleta de informações e dados para trazer aos usuários produtos e serviços personalizados, restringindo-se ao uso de métodos como câmeras e microfones, que pela percepção do usuário é uma ação muito invasiva. Desta maneira, resta ao profissional de Relações Públicas criar e segmentar estratégias certeiras e eficazes em campanhas para atingir públicos mais específicos, sem ferir a privacidade do usuário. [resumo fornecido pelo autor]
Keywords: Relações públicas; Direito à privacidade; Privacidade; Proteção de dados; Redes sociais on-line